Effect of Addition of Hydrocolloids on the Colloidal Stability of Litchi (Litchi chinensis Sonn.) Juice. Issue 2 (19th February 2014) - Babbar, Neha; Aggarwal, Poonam; Oberoi, Harinder Singh
Abstract This study aimed to evaluate the effect of addition of hydrocolloids, viz. carboxymethyl cellulose (CMC), sodium alginate (SA) and pectin, on cloud of the litchi juice. Among the three hydrocolloids, addition of pectin did not show a significant effect on the cloud stability whereas incorporation of 0.3% CMC and 0.2% SA had a profound influence on cloud stability of the litchi juice. Total solids, total soluble solids, specific gravity, viscosity and turbidity increased significantly in the juice containing hydrocolloids. This study has shown that the cloud retention during storage was maximum in juice containing CMC while addition of SA led to a partial settlement of the cloud, whereas in the control samples (where no hydrocolloid was added) it showed complete settlement. Practical Applications The present study was conducted with a major objective to evaluate the effect of addition of different hydrocolloids on cloud stability of the litchi juice and also to evaluate the physicochemical characteristics of the juice after incorporation of the selected hydrocolloid at the desired concentration. These days, consumers prefer the cloud stable juices as cloud imparts a characteristic flavor, color and mouthfeel. Previously published literature suggests that the litchi juice is highly unstable, therefore it requires incorporation of hydrocolloids for improving the cloud stability and maintaining cloud for a longer duration. This study showed that incorporation of 0.3% CMC not only increased viscosity and turbidity but also substantially improved the cloud stability in the litchi juice during storage over a period of 6 months. These results assume practical significance for the litchi juice manufacturers who could store the juice bottles with the desired cloud for longer durations.